Glyptik von Qubur al-Walaydah - Keel, Othmar (Die Welt des Orients, 2010)
The four seal-amulets documented by a scarab, a seal fragment and two seal impressions (one delt with by M. Schröder) are most probably all of Egyptian origin. While that has to be expected for the 13th century BCE, it is quite surprising for the first millennium.